Challenges of Implementing Green Entrepreneurship Education in the Classroom: An Exploratory Study - Eka Imbia Agus Diartika; Endah Rochmatika; Zahid Zufar At Thaariq (Jurnal Riset dan Inovasi Pembelajaran, 2026)
Green Entrepreneurship Education (GEE) plays a strategic role in fostering students' Green Entrepreneurial Intention (GEI) and Green Entrepreneurial Behavior (GEB) in support of sustainable development. However, the classroom-level implementation of GEE in higher education remains challenging. This study aims to explore the initial conditions of green entrepreneurship learning, classroom implementation challenges, and learning development needs in the Bioentrepreneurship Study Program. An exploratory qualitative approach was employed, with data collected through in-depth interviews with lecturers and students. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that lecturers perceive green entrepreneurship as highly urgent; However, learning practices remain predominantly theoretical, with limited experiential learning, insufficient facilities, and weak institutional support. Key barriers to the formation of students’ GEI and GEB include limited practical facilities, low entrepreneurial self-efficacy, lack of mentoring, capital constraints, and weak industry networks. These conditions reinforce the intention–behavior gap between students' green entrepreneurial intentions and actual behaviors. Based on these findings, this study recommends the development of an experience-based green entrepreneurship learning model that integrates project-based learning, structured mentoring, and institutional support through applied laboratories and industry collaboration to strengthen the translation of GEI into GEB. This study highlights the need to develop a more applicable, contextual, and experience-based green entrepreneurship learning model to strengthen GEI and GEB in higher education.